Maximizing Strategy with an Effective Balanced Scorecard - Endrianto, Wendy (Journal the Winners: Economics, Business, Management, and Information System Journal, 2016)
The research was conducted by studying the literature on the topic discussed. Presented descriptively in a systematic way to address each of the key discussion on this research, then connecting factors correlated with each other were finally seeking a conclusion the most effective method in meeting the company's goals. Then, through this study it can be concluded that in order to synergize between vision, mission and strategy of the company in regard to improving the company's performance is by communicating the balanced scorecard from top management down to the lower level of management so that all elements of the company know their respective roles in order to achieve company’s goal.